Mothers' Knowledge about Exclusive Breastfeeding Increases Self Efficacy in Breastfeeding to Mothers Post Sectio Caesarea - Sri Sat Titi Hamranani; Retnawati Retnawati; Sri Handayani; Devi Permatasari (GLOBAL HEALTH SCIENCE GROUP, 2024)
Breastfeeding is important interaction between mother and baby. Many mother have experience breastfeeding problems due to lack of knowledge and effect on the mother's psychology. Self-efficacy is one of the factors that influences the psychological level. Purpose to determine the relationship between the level of knowledge about breastfeeding and the level of self-efficacy in breastfeeding mothers after giving birth by caesarean section (SC). This research was conducted cross-sectionally on post-SC mothers at Wonosari Regional Hospital in August – October 2023 with accidental sampling method. Self-efficacy assessment was carried out using the Breastfeeding Self-Efficacy Scale-Short Form (BSES-SF). Assessment of the level of knowledge of breast milk is carried out by assessing four components, namely the understanding, composition, benefits and impact of exclusive breast milk by breastfeeding mothers. Bivariate analysis in this study used statistical tests with the Kendall Tau B test with a p value <0.05 indicating significant results. A total of 58 post-SC pregnant women took part in this study. The average age of respondents was 29.45 ± 6.506 years with an average gestational age of 38.98 ± 0.805 weeks. The majority of respondents had junior high school education (43.1%), were multiparous (58.6%), and did not work (74.1%). As many as 87.9% of respondents had good knowledge with 81% of respondents having a high level of self-efficacy. Kendall Tau analysis obtained a true P value of 0.001 with p < 0.05 with a strength of relationship of 0.435. There is knowledge about breastfeeding increased of self-efficacy in post-SC mothers at Wonosari Regional Hospital.